Meta-Analyzing Apples and Oranges: How to Make Applesauce Instead of Fruit Salad. - Carpenter, Christopher J (Human Communication Research)
This essay attempts to describe the apples and oranges problem in meta-analyses. Essentially, some meta-analyses combine original studies of various variables that are not the same pairs of variables. Metaphorically, they meta-analyze the effects of fruit when they should conduct separate meta-analyses of apples and oranges. This practice is inconsistent with the assumptions behind the meta-analytic formulae concerning sampling error and makes meta-analytic estimates difficult to interpret. Meta-analysis teams are advised to justify their choices and types of evidence are described to assist researchers and reviewers in assessing and justifying when constructs can and cannot be combined together in a meta-analysis.